Evaluate $\lim_{n\to\infty} \prod_{k=1}^n \frac{2k}{2k-1}\int_{-1}^{\infty} \frac{{\left(\cos{x}\right)}^{2n}}{2^x} \; dx$

Problem 9 in the JHMT 2013 Calculus Test asks to evaluate $$\lim_{n\to\infty} \prod_{k=1}^n \frac{2k}{2k-1}\int_{-1}^{\infty} \frac{{\left(\cos{x}\right)}^{2n}}{2^x} \; dx$$ The answer is $$\pi\cdot 2^\pi /(2^{\pi}-1)$$. How can I show this? I know that the infinite product diverges and the limit cannot be moved into the integral, but I don't know what to do. Maybe I can represent the integral as a summation?

• The product is asymptotically $e^{-\sum_k \log (1-\frac{1}{2k}}) = (e^{H_n})^{\frac{1}{2}} \sim \sqrt{n}$
– Alex
May 23, 2020 at 14:20
• @Alex I still don't understand how I can use that to solve the integral
– Ty.
May 23, 2020 at 16:35
• @EeyoreHo JHMT 2013 Problem #9 math.jhu.edu/~mathclub/problems/problems2013/Calculus.pdf
– Ty.
May 23, 2020 at 20:16
• Sometimes when I get too full of my self, I look at problems like this with a suggested $5$ minute time to complete it, and I return to normal. May 23, 2020 at 21:12
• It may be that the integral runs from $-\pi$ and not from $-1$. In this case one could simplify a bit the expression by splitting the integral into subintervals, but I was not able to arrive yet to a solution. May 23, 2020 at 21:42

The identities $$\frac{2\cdot4\cdot\ldots\cdot (2n)}{1\cdot3\cdot\ldots\cdot(2n-1)}=\frac{\Gamma(n+1)}{\Gamma(n+\tfrac12)}\sqrt{\pi}$$ and Wallis' formula $$\int^{\frac{\pi}{2}}_0\cos^{2n}x\,dx=\int^{\frac{\pi}{2}}_0\sin^{2n}(x)\,dx=\frac{\Gamma(n+\tfrac12)}{\sqrt{\pi}\Gamma(n+1)}\frac{\pi}{2}$$ will be useful ( a simple derivation of the latter is in Thenard Rinmann's solution). The sequence in your problem can be expressed as $$I_n:=\frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^\infty_{-1}2^{-x}\cos^{2n}x\,dx$$ To make estimates simpler, I only consider the sequence $$J_n:=\frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^\infty_0 2^{-x}\cos^{2n}x\,dx$$ The integral $$\int^\infty_0 2^{-x}\cos^{2n}x\,dx$$ can be expressed as \begin{aligned} \int^\infty_0 2^{-x}\cos^{2n}x\,dx&=\sum^\infty_{k=0}\int^{(k+1)\pi}_{k\pi}2^{-x}\cos^{2n}x\,dx=\sum^\infty_{k=0}\int^\pi_02^{-(x+ k\pi)}\cos^{2n}(x+k\pi)\,dx \\&=\Big(\sum^\infty_{k=0}2^{-k\pi}\Big)\int^\pi_02^{-x}\cos^{2n}x\,dx=\frac{1}{1-2^{-\pi}}\int^\pi_02^{-x}\cos^{2n}xdx \end{aligned} Here we have used the fact that $$\cos(x+k\pi)=(-1)^k\cos(x)$$.

Claim I: $$\frac{\Gamma(n+1)}{\Gamma(n+\tfrac12)}\sim\sqrt{n}$$. This follows from Stirling's approximation: $$\frac{\Gamma(n+1)}{\Gamma(n+\tfrac12)}\sim \frac{n^{n+\tfrac12}e^{-n}}{(n-\tfrac12)^n e^{-(n-\tfrac12)}}$$

Claim II: (Suggested by Raoul below) $$\int^{\pi/2}_02^{-x}\cos^{2n}x\,dx=\int^{\pi/2}_0\cos^{2n}x\,dx + o(n^{-1/2})$$. To check this, we apply the mean value theorem to get \begin{aligned} \Big|\int^{\pi/2}_0(1-2^{-x})\cos^{2n}x\,dx\Big|\leq \log2\int^{\pi/2}_0x\cos^{2n}x\,dx \end{aligned} The fact that $$\frac{\sin x}{x}$$ decreases over $$[0,\pi]$$, implies that $$\frac{2}{\pi}x-\sin x\leq0$$ on $$[0,\pi/2]$$ and so, $$\frac{x^2}{\pi}+\cos x\leq 1$$. Consequently \begin{aligned} \int^{\pi/2}_0x\cos^{2n}x\,dx&\leq \int^{\pi/2}_0x\Big(1-\frac{x^2}{\pi}\Big)^{2n}\,dx\\ &=\frac{\pi}{2}\int^{\pi/4}_0(1-u)^{2n}\,du=\frac{\pi}{2(2n+1)}\Big(1-\big(1-\tfrac{\pi}{4}\big)^{2n+1}\Big) \end{aligned} This proves the claim.

A similar argument shows that \begin{aligned} \int^\pi_{\pi/2}2^{-x}\cos^{2n}x\,dx&=2^{-\pi}\int^0_{-\pi/2}2^{-x}\cos^{2n}(x+\pi)\,dx\\ &=2^{-\pi}\int^{\pi/2}_02^x\cos^{2n}x\,dx=2^{-\pi}\int^{\pi/2}_0\cos^{2n}x\,dx+o(n^{-1/2}) \end{aligned}

It follows that \begin{aligned} J_n&=\frac{1}{1-2^{-\pi}} \frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\frac12)}\Big((1+2^{-\pi})\int^{\pi/2}_0\cos^{2n}x\,dx+o(n^{-1/2})\Big)\\ &=\frac{2^\pi}{2^\pi-1}(1+2^{-\pi})\frac{\pi}{2}+o(1) \end{aligned}

The contribution of $$\frac{\sqrt{\pi}\,\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^0_{-1}2^{-x}\cos^{2n}x\,dx$$ can also be estimated as follows $$\int^0_{-1}2^{-x}\cos^{2n}x\,dx=\int^1_02^x\cos^{2n}x\,dx=\int^{\tfrac{\pi}{2}}_02^x\cos^{2n}x\,dx-\int^{\frac{\pi}{2}}_12^{x}\cos^{2n}x\,dx$$ The second term is bounded by $$\int^{\frac{\pi}{2}}_12^x\cos^{2n}x\,dx\leq (\cos 1)^{2n}\Big(\frac{\pi}{2}-1\Big)2^{\pi/2}=o(n^{-1/2})$$ Consequently \begin{aligned} \frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^0_{-1}2^{-x}\cos^{2n}x\,dx&=\left(\frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^{\pi/2}_02^{x}\cos^{2n}x\,dx\right) +o(1)\\ &=\left(\frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\Big(\int^{\pi/2}_0\cos^{2n}x\,dx+o(n^{-1/2})\Big)\right) +o(1)\\ &=\frac{\pi}{2}+o(1) \end{aligned}

Putting things together gives $$I_n=J_n+\frac{\sqrt{\pi}\Gamma(n+1)}{\Gamma(n+\tfrac12)}\int^0_{-1}2^{-x}\cos^{2n}x\,dx=\pi\frac{2^\pi}{2^\pi-1} +o(1)$$

• @Raoul . By applying the m.v.t. on $f(x)=2^{-x}$ I get $(1-2^{-x})\le ( sup_{z \ in [0,x]}2^{-z}) x=x$. So that $1-2^{-x} \le x$ for $x>0$ which can also be proven by other means. Does this mean that $C_1=1$ ? Oliver Diaz, why do you have $C_1=log(2)$ ? I know the value of the constant is not important but just for clarification. May 24, 2020 at 9:52
• By the way very nice solution putting together a lot of nice ideas. I had just spot the geometric sum than I was blocked :) May 24, 2020 at 10:20
• @Thomas Yes, you are missing a $\ln 2$ in the derivative of $2^{-x}$ to apply the MVT. And much cleaner solution from Oliver to bound the error, nicely done. May 24, 2020 at 14:27
• You are right I forgot the prefactor in deriving $2^{-x}$. Bad mistake from my side but thanks for clarifying. Again, nice solution :) May 24, 2020 at 14:40

Rewrote the proof

We first give the following auxiliary results (Facts 1 through 2). The proofs are given at the end.

Fact 1: It holds that $$\int_{-1}^\infty \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x = \frac{2^\pi}{2^\pi - 1}\int_{-1}^{\pi-1} \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x.$$

Fact 2: It holds that, for all $$-1 \le x \le 1$$ and $$n \ge 2$$, $$\mathrm{e}^{-x^2n} - \frac{1}{n} \le (\cos x)^{2n} \le \mathrm{e}^{-x^2n}.$$

Now, by Stirling formula $$n! \sim \sqrt{2\pi n}\ n^n \mathrm{e}^{-n}$$, we have $$\prod_{k=1}^n \frac{2k}{2k-1} = \frac{2^{2n}(n!)^2}{(2n)!} \sim \frac{2^{2n}(\sqrt{2\pi n}\ n^n \mathrm{e}^{-n})^2}{\sqrt{2\pi \cdot 2n}\ (2n)^{2n} \mathrm{e}^{-2n}}= \sqrt{\pi n}.$$ Then, by Facts 1-2, we have \begin{align} &\lim_{n\to \infty} \left(\prod_{k=1}^n \frac{2k}{2k-1}\cdot \int_{-1}^\infty \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\right)\\ =\ & \lim_{n\to \infty} \left(\sqrt{n\pi}\cdot \frac{2^\pi}{2^\pi - 1}\int_{-1}^{\pi-1} \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\right)\\ =\ & \pi\frac{2^\pi}{2^\pi-1} \cdot \lim_{n\to \infty} \left(\int_{-1}^1 \frac{(\cos x)^{2n}}{2^x} \sqrt{\frac{n}{\pi}}\, \mathrm{d}x + \int_1^{\pi-1} \frac{(\cos x)^{2n}}{2^x} \sqrt{\frac{n}{\pi}}\, \mathrm{d}x\right)\\ =\ & \pi\frac{2^\pi}{2^\pi-1} \cdot \lim_{n\to \infty} \int_{-1}^1 \frac{\mathrm{e}^{-x^2n}}{2^x} \sqrt{\frac{n}{\pi}}\, \mathrm{d}x\\ =\ & \pi\frac{2^\pi}{2^\pi-1} \cdot \lim_{n\to \infty} \exp\left(\tfrac{(\ln 2)^2}{4n}\right) \int_{-\sqrt{\frac{n}{\pi}} + \frac{\ln 2}{2\sqrt{\pi n}}}^{\sqrt{\frac{n}{\pi}} + \frac{\ln 2}{2\sqrt{\pi n}}} \mathrm{e}^{-\pi z^2} \mathrm{d}z\\ =\ & \pi\frac{2^\pi}{2^\pi-1} \cdot \int_{-\infty}^\infty \mathrm{e}^{-\pi z^2} \mathrm{d}z\\ =\ & \pi\frac{2^\pi}{2^\pi-1} \end{align} where we have used $$\lim_{n\to \infty} \int_1^{\pi-1} \frac{(\cos x)^{2n}}{2^x} \sqrt{\frac{n}{\pi}}\, \mathrm{d}x = 0$$ by noting that $$|\cos x| \le \cos 1 < \frac{3}{5}$$ for all $$x$$ in $$[1, \pi - 1]$$.

$$\phantom{2}$$

Proof of Fact 1: We have \begin{align} &\int_{-1}^\infty \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\\ =\ & \int_{-1}^0 \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x + \sum_{j=0}^\infty \int_{j\pi}^{(j+1)\pi} \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\\ =\ & \int_{-1}^0 \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x + \sum_{j=0}^\infty \frac{1}{2^{j\pi}}\int_0^\pi \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\\ =\ & \int_{-1}^0 \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x + \frac{2^\pi}{2^\pi - 1}\int_0^\pi \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x \\ =\ & \int_{-1}^0 + \frac{2^\pi}{2^\pi - 1} \left(\int_{-1}^{\pi-1} + \int_{\pi-1}^\pi - \int_{-1}^0\right) \\ =\ & \frac{2^\pi}{2^\pi - 1}\int_{-1}^{\pi-1} + \frac{2^\pi}{2^\pi - 1}\int_{\pi-1}^\pi -\frac{1}{2^\pi-1}\int_{-1}^0 \tag{1} \\ =\ & \frac{2^\pi}{2^\pi - 1}\int_{-1}^{\pi-1} + \frac{1}{2^\pi - 1}\int_{-1}^0 -\frac{1}{2^\pi-1}\int_{-1}^0 \tag{2} \\ =\ & \frac{2^\pi}{2^\pi - 1}\int_{-1}^{\pi-1} \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x. \end{align} In (1)(2) we have used $$\int_{\pi-1}^\pi \frac{(\cos x)^{2n}}{2^x}\mathrm{d}x = \frac{1}{2^\pi} \int_{-1}^0 \frac{(\cos y)^{2n}}{2^y}\mathrm{d}y$$ (by the substitution $$x - \pi = y$$). We are done.

Proof of Fact 2: The right inequality is equivalent to $$\ln \cos x \le - \frac{x^2}{2}.$$ The proof is easy and thus omitted.

For the left inequality, clearly, we only need to prove the case when $$-\sqrt{\frac{\ln n}{n}} < x < \sqrt{\frac{\ln n}{n}}$$. The left inequality is equivalent to $$\ln \left(\mathrm{e}^{-x^2n} - \frac{1}{n}\right) \le 2n\ln \cos x$$ or $$-x^2n + \ln \Big(1 - \frac{\mathrm{e}^{x^2n}}{n}\Big) \le 2n\ln \cos x.$$ Since $$\ln (1 - \frac{\mathrm{e}^{x^2n}}{n}) \le - \frac{\mathrm{e}^{x^2n}}{n}$$ and $$\cos x \ge 1 - \frac{x^2}{2}$$, it suffices to prove that $$-x^2n - \frac{\mathrm{e}^{x^2n}}{n} \le 2n\ln \left(1-\frac{x^2}{2}\right).$$ Let $$F(x) = 2n\ln \left(1-\frac{x^2}{2}\right) + x^2n + \frac{\mathrm{e}^{x^2n}}{n}.$$ We have $$F'(x) = \frac{2x}{2-x^2}\left(\mathrm{e}^{x^2n}(2-x^2) - x^2n\right).$$ Since $$\mathrm{e}^{x^2n}(2-x^2) - x^2n \ge \mathrm{e}^{x^2n} - x^2n > 0$$, we have $$F'(x) > 0$$ for $$0 < x < \sqrt{\frac{\ln n}{n}}$$, and $$F'(x) < 0$$ for $$-\sqrt{\frac{\ln n}{n}} < x < 0$$. Also, $$F(0) > 0$$. Thus, $$F(x) \ge 0$$ for $$-\sqrt{\frac{\ln n}{n}} < x < \sqrt{\frac{\ln n}{n}}$$. We are done.

• (+1) You might consider stating how you arrived at $(1)$. Also, you need to explain how $(2)$ is valid rigoroulsy. You are likely using $\cos(x)=1-\frac12 x^2+O(x^3)$, but not that this is valid for $x$ "near" $0$. May 24, 2020 at 17:00
• @MarkViola Thanks. I will update it. May 25, 2020 at 0:40

I think it's simpler to evaluate the integral like this: $$\$$ We know that by Wallis formula $$\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}(\cos x)^{2n}=I_n=\frac{2n-1}{2n}I_{n-1}$$ which on recursive application gives us $$I_n=I_0\prod_{k=1}^n\frac{2k-1}{2k}$$ which gives d$$I_n=\pi\prod_{k=1}^n\frac{2k-1}{2k} \space (\text{as}\space I_0=\pi)$$ and as $$n\to\infty$$ the value of $$\int_{-1}^{\infty}\frac{(\cos x)^{2n}}{2^x}\mathrm{d}x$$ will get concentrated near the values where $$\cos x$$ becomes $$+1$$ or $$-1$$ and that happens at $$0,\pi,2\pi,\ldots$$ and the area near other parts of the graph will tend to zero . (I understand that this isn't the most rigorous way to put it, but I believe such ideas are based off the Dominated Convergence Theorem, which I am not very familiar with.) However, answers provided by Oliver Diaz and and River Li give a firm proof for this reasoning. Do look through them for thorough assurance of the idea. For $$n=10^{9}$$the graph is like this(from desmos)So, we can write the integral as $$\sum_{k=0}^{\infty}\frac{I_n}{2^{k\pi}}$$ and the total value as $$n\to \infty$$ becomes equal to $$\prod_{k=1}^n\frac{2k}{2k-1}\int_{-1}^{\infty}\frac{(\cos x)^{2n}}{2^x}\mathrm{d}x\to \prod_{k=1}^n\frac{2k}{2k-1}\sum_{k=0}^{\infty}\frac{I_n}{2^{k\pi}}=\frac{\pi}{1-2^{-\pi}}=\frac{\pi2^{\pi}}{2^{\pi}-1}$$ and this is valid as long as the lower limit of the integral $$\int_{-1}^{\infty}\frac{(\cos x)^{2n}}{2^x}\mathrm{d}x$$ more than -$$\pi$$ and if it's less than $$-\pi$$ then the lower limit of the summation will become $$k=-1$$ instead of $$k=0$$

• I didn't think of using Wallis formula, that was good.
– Ty.
May 26, 2020 at 14:50
• You intuitive idea is very good. However more careful analysis is required. Dominated convergence shows that $a_n=\int^0_{-1}2^{-x}\cos^{2n}x\,dx\xrightarrow{n\rightarrow\infty}0$. On the other hand the product $b_n=\prod^n_{k-1}\frac{2k-1}{2n}\sim\sqrt{n}\xrightarrow{n\rightarrow\infty}\infty$. That is why a careful analysis of the rate of convergence of the factor $a_n$ is needed to balanced the competing factor $b_n$ that is growing. May 26, 2020 at 22:21

Firstly split it up into two parts: $$\prod_{k=1}^n\frac{2k}{2k-1}=\frac{2.4.6.8...2n}{1.3.5.7.(2n-1)}=\frac{2^nn!\times2^{n-1}(n-1)!}{(2n-1)!}=\frac{2^{2n-1}n!(n-1)!}{(2n-1)!}=\frac{2^{2n-1}(n!)^2}{n(2n-1)!}$$ now the integral: $$I_n=\int_{-1}^\infty\frac{(\cos x)^{2n}}{2^x}dx$$ $$I_n(a)=\int_{-1}^\infty e^{-ax}\cos^{2n}xdx$$ and we know that: $$\cos^{2n}x=\frac{(e^{ix}+e^{-x})^{2n}}{2^{2n}}$$ and: $$(e^{ix}+e^{-ix})^{2n}=\sum_{r=0}^{2n}{{2n}\choose{r}}e^{(2n-r)ix}e^{-rix}=\sum_{r=0}^{2n}{{2n}\choose{r}}e^{(2n-2r)ix}$$ so our integral becomes: $$I_n(a)=\int_{-1}^\infty\sum_{r=0}^{2n}{{2n}\choose{r}}e^{(2n-2r)ix-ax}dx=I_n(a)=\int_{-1}^\infty\sum_{r=0}^{2n}{{2n}\choose{r}}e^{(2i(n-r)-a)x}dx$$ assuming we can interchange the integral and summation and allowing $$-b=2i(n-r)-a$$ we get: $$I_n(a)=\sum_{r=0}^{2n}{{2n}\choose{r}}\int_{-1}^\infty e^{-bx}dx=\sum_{r=0}^{2n}{{2n}\choose{r}}\left[\frac{-e^{-bx}}{b}\right]_{-1}^\infty=\sum_{r=0}^{2n}{{2n}\choose{r}}\frac{e^b}{b}$$ $$I_n(a)=\sum_{r=0}^{2n}{{2n}\choose{r}}\frac{e^{a-2i(n-r)}}{a-2i(n-r)}$$ If we bring it all together we get: $$L=\lim_{n\to\infty}\frac{2^{2n-1}(n!)^2}{n(2n-1)!}\sum_{r=0}^{2n}{{2n}\choose{r}}\frac{e^{\ln(2)-2i(n-r)}}{\ln(2)-2i(n-r)}$$ and we know that: $${2n\choose r}=\frac{(2n)!}{r!(2n-r)!}=\frac{2^nn!}{r!(2n-r)!}$$ so: $$L=\lim_{n\to\infty}\frac{2^{3n}(n!)^3}{n(2n-1)!}\sum_{r=0}^{2n}\frac{e^{-2i(n-r)}}{\ln(2)-2i(n-r)}\times\frac{1}{r!(2n-r)!}$$

• With respect, I don't feel this is a satisfactory answer. It is not at all obvious the final limit is what the OP claims it is. May 23, 2020 at 21:04
• @OliverDiaz I rewrote the summation part in the question because I didn't think it was what OP was really trying to ask, but now I see I was a bit hasty on that. May 24, 2020 at 15:03

$$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\on}[1]{\operatorname{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$$ $$\ds{\bbox[5px,#ffd]{\lim_{n \to\infty}\,\, \prod_{k = 1}^{n}{2k \over 2k - 1} \int_{-1}^{\infty}{\cos^{2n}\pars{x} \over 2^x} \,\dd x = {2^\pi \over 2^{\pi} - 1}\,\pi} \approx 3.5431:\ {\Large ?}}$$.

\begin{align} &\bbox[5px,#ffd]{\prod_{k = 1}^{n}{2k \over 2k - 1}} = \prod_{k = 1}^{n}{k \over k - 1/2} = {n! \over \pars{1/2}^{\overline{n}}} \\[5mm] = &\ {n! \over \Gamma\pars{1/2 + n}/\Gamma\pars{1/2}} = \root{\pi}{n! \over \pars{n - 1/2}!} \\[5mm] &\ \,\,\,\stackrel{\mrm{as}\ n\ \to\ \infty}{\sim}\,\,\, \root{\pi}{\root{2\pi}n^{n + 1/2}\,\,\expo{-n} \over \root{2\pi}\pars{n - 1/2}^{n}\expo{-n + 1/2}} \\[5mm] = &\ \root{\pi}{n^{n + 1/2} \over n^{n}\,\bracks{1 - \pars{1/2}/n}^{\,n}\expo{1/2}} \\[5mm] & \stackrel{\mrm{as}\ n\ \to\ \infty}{\sim}\,\,\, \bbx{\root{\pi}n^{1/2}}\label{1}\tag{1} \\ & \end{align}
\begin{align} &\bbox[5px,#ffd]{ \int_{-1}^{\infty}{\cos^{2n}\pars{x} \over 2^x} \,\dd x} \\[5mm] = &\ \int_{-1}^{0}2^{-x}\cos^{2n}\pars{x}\,\dd x + \sum_{k = 0}^{\infty}\,\,\int_{k\pi}^{k\pi + \pi}2^{-x} \cos^{2n}\pars{x}\,\dd x \\[5mm] = &\ \int_{0}^{1}2^{x}\cos^{2n}\pars{x}\,\dd x + \sum_{k = 0}^{\infty}\,\,2^{-k\pi} \int_{0}^{\pi}2^{-x}\cos^{2n}\pars{x}\,\dd x \\[5mm] = &\ \underbrace{\int_{0}^{1}2^{x}\cos^{2n}\pars{x}\,\dd x} _{\ds{\cal I}}\ +\ {1 \over 1 - 2^{-\pi}}\ \underbrace{\int_{0}^{\pi}2^{-x}\cos^{2n}\pars{x} \,\dd x}_{\ds{\cal J}} \end{align}

In order to evaluate the asymptotic integrals; I'll use, hereafter, the Laplace's Method: \begin{align} {\cal I} & \equiv \int_{0}^{1}2^{x}\cos^{2n}\pars{x}\,\dd x = \int_{0}^{1}2^{x}\exp\pars{2n\ln\pars{\cos\pars{x}}} \,\dd x \\[5mm] &\ \stackrel{\mrm{as}\ n\ \to\ \infty}{\sim}\,\,\, \int_{0}^{\infty}\exp\pars{-nx^{2}}\dd x = {\root{\pi} \over 2}\,n^{-1/2} \end{align} Similarly, \begin{align} {\cal J} & \equiv \int_{0}^{\pi}2^{-x}\cos^{2n}\pars{x}\,\dd x = \int_{-\pi/2}^{\pi/2}2^{-x - \pi/2}\,\, \sin^{2n}\pars{x}\,\dd x \\[5mm] = &\ 2^{-\pi/2}\int_{0}^{\pi/2}\pars{2^{-x} + 2^{x}} \sin^{2n}\pars{x}\,\dd x \\[5mm] = &\ 2^{-\pi/2}\int_{0}^{\pi/2}\pars{2^{-\pi/2 + x}\ +\ 2^{\pi/2 - x}} \cos^{2n}\pars{x}\,\dd x \\[5mm] &\ \stackrel{\mrm{as}\ n\ \to\ \infty}{\sim}\,\,\, \pars{2^{-\pi} + 1}\int_{0}^{\infty} \exp\pars{-nx^{2}}\dd x \\[5mm] = &\ \pars{2^{-\pi} + 1}{\root{\pi} \over 2}\,n^{-1/2} \end{align} Then, \begin{align} &\bbox[5px,#ffd]{ \int_{-1}^{\infty}{\cos^{2n}\pars{x} \over 2^x} \,\dd x} \\[5mm] \stackrel{\mrm{as}\ n\ \to\ \infty}{\sim}\,\,\, &\ \overbrace{{\root{\pi} \over 2}\,n^{-1/2}} ^{\ds{\sim {\cal I}\ \mrm{as}\ n\ \to\ \infty}} \\[2mm] + &\ {1 \over 1 - 2^{-\pi}}\ \underbrace{\pars{2^{-\pi} + 1}\, {\root{\pi} \over 2}\,n^{-1/2}} _{\ds{\sim {\cal J}\ \mrm{as}\ n\ \to\ \infty}} \\[5mm] = &\ \bbx{{\root{\pi} \over n^{1/2}} \,{2^{\pi} \over 2^{\pi} - 1}} \label{2}\tag{2} \\ & \end{align}

With (\ref{1}) and (\ref{2}): \begin{align} &\bbox[5px,#ffd]{\lim_{n \to\infty}\,\, \prod_{k = 1}^{n}{2k \over 2k - 1} \int_{-1}^{\infty}{\cos^{2n}\pars{x} \over 2^x} \,\dd x} = \bbx{{2^\pi \over 2^{\pi} - 1}\,\pi} \\[5mm] \approx &\ 3.5431 \end{align}
• The details for applying the Laplace's method are omitted. Also, a typo after "Similarly". Nov 15, 2020 at 6:23
• @RiverLi Fixed. Thanks. Basically, both integrals (after rearranging them) yield the "main contribution" when $\displaystyle x \gtrsim 0$. In order to use Laplace, we write $\displaystyle \cos^{2n}\,\left(x\right) = \exp\left(2n\ln\left(\cos\left(x\right)\right)\right) \sim \exp\left(2n\ln\left(1 - {x^{2} \over 2}\right)\right) \sim \exp\left(2n\left[- {x^{2} \over 2}\right]\right) = \exp\left(-nx^{2}\,\right)$. The remaining factors are evaluated at $\displaystyle x = 0$: That's basically Laplace. Nov 15, 2020 at 6:48
• I know the Laplace method. Also, clearly, your proof is correct. However, from a rigorous point of view, if your write down the details, your proof is actually very long. Nov 15, 2020 at 7:04
• @RiverLi That's true and that's the reason why links are useful. We expect that the interested reader "polishes" the details with the link. Thanks. I go to sleep. Good night. Nov 15, 2020 at 7:25

Basically the same idea as Thenard Rinmanns answer using the Wallis formula, but more rigorous.

First of all $$\prod_{k=1}^n \frac{2k}{2k-1} \leq \frac{\prod\limits_{k=1}^n 2k}{\prod\limits_{k=2}^n(2k-2)}=2n \, ,$$ thus $$\prod_{k=1}^n \frac{2k}{2k-1}\int_{-\pi/2}^{-1} \frac{{\left(\cos{x}\right)}^{2n}}{2^x} \, {\rm d}x\leq 2n \cos(1)^{2n}(\pi/2-1)2^{\pi/2}$$ which vanishes in the limit $$n\to\infty$$. We can therefore equally consider $$\int_{-\pi/2}^{\infty} \frac{{\left(\cos{x}\right)}^{2n}}{2^x} \, {\rm d}x = \sum_{k=0}^\infty \int_{k\pi-\pi/2}^{k\pi+\pi/2} \frac{(\cos x)^{2n}}{2^x} \, {\rm d}x \stackrel{x=k\pi+t}{=} \sum_{k=0}^\infty 2^{-k\pi} \int_{-\pi/2}^{\pi/2} \frac{(\cos t)^{2n}}{2^t} \, {\rm d}t \, .$$ Now, $$\forall \epsilon >0$$ we have $$\prod_{k=1}^n \frac{2k}{2k-1} \int\limits_{\epsilon \leq |t| \leq \pi/2} \frac{(\cos t)^{2n}}{2^t} \, {\rm d}t \leq 2n (\cos \epsilon)^{2n} 2^{\pi/2} \pi$$ which vanishes in the limit $$n\to\infty$$ for all $$\epsilon >0$$. As such $$\prod_{k=1}^{n} \frac{2k}{2k-1} \int_{-1}^{\infty} \frac{(\cos x)^{2n}}{2^x} \, {\rm d}x = \frac{1}{1-2^{-\pi}} \prod_{k=1}^{n} \frac{2k}{2k-1} \int_{-\epsilon}^{\epsilon} \frac{(\cos t)^{2n}}{2^t} \, {\rm d}t + O(n\cos(\epsilon)^{2n})\\ = \frac{2^{-t_0}}{1-2^{-\pi}} \prod_{k=1}^{n} \frac{2k}{2k-1} \int_{-\epsilon}^{\epsilon} (\cos t)^{2n} \, {\rm d}t + O(n\cos(\epsilon)^{2n}) \\ = \frac{2^{-t_0}}{1-2^{-\pi}} \prod_{k=1}^{n} \frac{2k}{2k-1} \underbrace{\int_{-\pi/2}^{\pi/2} (\cos t)^{2n} \, {\rm d}t}_{\pi\prod\limits_{k=1}^n \frac{2k-1}{2k}} + O(n\cos(\epsilon)^{2n}) = \frac{\pi \, 2^{-t_0}}{1-2^{-\pi}} + O(n\cos(\epsilon)^{2n})$$ for some $$t_0\in(-\epsilon,\epsilon)$$ by the MVT. Since this is true $$\forall \epsilon>0$$, the claim follows.

• Can someone explain to me why the downvotes? Jun 12, 2023 at 10:13